Redefining viability by cardiovascular magnetic resonance in acute ST-segment elevation myocardial infarction. Issue 1 (December 2017) - Bulluck, Heerajnarain; Rosmini, Stefania; Abdel-Gadir, Amna; Bhuva, Anish; Treibel, Thomas; Fontana, Marianna; Knight, Daniel; Nordin, Sabrina; Sirker, Alex; Herrey, Anna; Manisty, Charlotte; Moon, James; et al.
Abstract In chronic myocardial infarction (MI), segments with a transmural extent of infarct (TEI) of ≤50% are defined as being viable. However, in the acute phase of an ST-segment elevation myocardial infarction (STEMI), late gadolinium enhancement (LGE) has been demonstrated to overestimate MI size and TEI. We aimed to identify the optimal cut-off of TEI by cardiovascular magnetic resonance (CMR) for defining viability during the acute phase of an MI, using ≤50% TEI at follow-up as the reference standard. 40 STEMI patients reperfused by primary percutaneous coronary intervention (PPCI) underwent a CMR at 4 ± 2 days and 5 ± 2 months. The large majority of segments with 1–25%TEI and 26–50%TEI that were viable acutely were also viable at follow-up (59/59, 100% and 75/82, 96% viable respectively). 56/84(67%) segments with 51–75%TEI but only 4/63(6%) segments with 76–100%TEI were reclassified as viable at follow-up. TEI on the acute CMR scan had an area-under-the-curve of 0.87 (95% confidence interval of 0.82 to 0.91) and ≤75%TEI had a sensitivity of 98% but a specificity of 66% to predict viability at follow-up. Therefore, the optimal cut-off by CMR during the acute phase of an MI to predict viability was ≤75% TEI and this would have important implications for patients undergoing viability testing prior to revascularization during the acute phase.